Fault-tolerant scheduling algorithm for real-time tasks in virtualized cloud - Ji WANG; Wei-dong BAO; Xiao-min ZHU (Tongxin xuebao)
In order to achieve the high reliability of real-time systems in virtualized clouds,a fault-tolerant scheduling algorithm for virtualized clouds named FSVC that used primary-backup approach to tolerate physical host failures was proposed.FSVC strived to enhance the performance by employing backup-backup overlapping technique and virtual Machine migration technique.The constraints of the two techniques were elaborately analyzed to realize fault tolerance.Besides,a two-phase policy was incorporated in FSVC to further improve the performance.Simulation experiments demonstrated that FSVC can improve the schedulability and resource utilization effectively in virtualized clouds.